THE IMPORTANCE OF RECONSTRUCTIVE PLASTIC SURGERY IN POST-TRAUMATIC SITUATIONS - Pedro do Valle Varela, João; Silva Paes, Ian; Machado Kallas Arantes, Nathália; Vitor Amorim Barbosa, João; Giselle Batt, Jennifer; Fairana Godeline Essali, Genese; Vettorazzi Zambom, Gabriel; Lobato Ferreira, Juliana; Nogueira Domingues, Shayanne; Luiz Teixeira Fully, Fabio (Health and Society, 2024)
Restorative plastic surgery plays a crucial role in restoring form and function to areas of the body affected by trauma. The main aim of this specialty is to improve patients’ quality of life and self-esteem, providing satisfactory aesthetic and functional results. This paper aims to explore and highlight the importance of reconstructive plastic surgery in post-traumatic situations, emphasizing its benefits for patients’ physical and psychological recovery. This is a bibliographic review, using qualitative premises, with the PubMed, Scopus, Web of Science and Scielo databases. To better refine the research, the health descriptors “trauma”, “reconstructive surgery” and “reconstructive plastic surgery after trauma” were used. Restorative plastic surgery is essential for reconstructing areas of the body affected by trauma, such as burns, traumatic wounds, car accidents and firearm injuries. As well as restoring function and aesthetics, these procedures can also improve patients’ quality of life and self-image. Common procedures include soft tissue reconstruction, skin grafts, flaps and reconstructive microsurgery. These techniques allow complex anatomical structures such as bones, muscles, nerves and blood vessels to be restored, re-establishing the functionality and natural appearance of the affected region. As a result, in addition to the physical benefits, reconstructive plastic surgery can also have a significant impact on patients’ mental health. Improved physical appearance can increase self-esteem and confidence, helping with social reintegration and a return to daily activities. It can therefore be concluded that reconstructive plastic surgery plays a vital role in the recovery of patients after trauma, providing not only physical restoration, but also improved quality of life and psychological well-being. It is essential that patients have access to these procedures and that health professionals are aware of their importance in post-traumatic rehabilitation.